2019
DOI: 10.1080/21691401.2018.1556213
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hesperetin loaded nanoparticles for anticancer activity against C6 glioma cancer cells

Abstract: The aim of this study was to evaluate anti-cancer properties of hesperetin (Hsp) and hesperetin-loaded poly(lactic-co-glycolic acid) nanoparticles (HspNPs) for glioblastoma treatment. Nanoparticles prepared by single emulsion method had a size of less than 300 nm with 70.7 ± 3.9% reaction yield and 26.4 ± 1.1% Hsp loading capacity. Treatment of C6 glioma cells with HspNPs for 24 and 48 h resulted in dose-and time-dependent decrease in cell viability, with approximate IC 50 of 28 and 21 lg/mL, respectively (p ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Wang et al reported that hesperetin was likely to act as an accelerator for the anti-cancer effect of DDP in lung adenocarcinoma ( Wang et al, 2019 ). Although there is growing evidence that hesperetin induces apoptosis in different types of cancer cells ( Ersoz et al, 2019 ; Li et al, 2019 ), whether hesperetin can enhance the chemical sensitivity of GC to DDP, and its specific mechanism, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al reported that hesperetin was likely to act as an accelerator for the anti-cancer effect of DDP in lung adenocarcinoma ( Wang et al, 2019 ). Although there is growing evidence that hesperetin induces apoptosis in different types of cancer cells ( Ersoz et al, 2019 ; Li et al, 2019 ), whether hesperetin can enhance the chemical sensitivity of GC to DDP, and its specific mechanism, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways can initiate caspase family proteins, including Caspase-3, Caspase-7, Caspase-8, etc. These proteins activate deoxyribonuclease, leading to chromosomal DNA fragmentation during apoptosis [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, U87 glioma cells were treated with OA nano or normal OA at different concentrations (10,20,30,40,50,60,70, 80 μmol/L) during designated time period to verify their therapeutic effects. In OA nano group, 50% of U87 glioma cells lost their activity (IC 50 ) at 35 μmol/L (Fig.…”
Section: Construction Of Oa Nano and Evaluation Of Its Therapeutic Efmentioning
confidence: 99%
“…It is derived from the young citrus fruit of the genus rutaceae . Recent studies showed that HES had antioxidant and anti‐cancer effects and it also modulated immune responses . So far, there has been no research on hesperetin as an adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent studies showed that HES had antioxidant and anti-cancer effects and it also modulated immune responses. [17][18][19] So far, there has been no research on hesperetin as an adjuvant. Therefore, we investigated the potential use of hesperetin as a B16F10 melanoma vaccine adjuvant.…”
Section: Introductionmentioning
confidence: 99%